Exploring the Impact of Parental Knowledge and Attitudes on Mediation Practices in Digital Parenting for Early Childhood - Erhamwilda; Afrianti, Nurul; Fitroh Hayati; Awit Marwati Sakinah; Salma Hanifa; Hirza (Universitas Pendidikan Ganesha, 2025)
Parents of young children are in a dilemma, on the one hand encouraging their children to use digital media for educational and social purposes. On the other hand, parents try to minimize risks and control the possible negative impacts of digital media use on them. Parental mediation is a parenting strategy to reduce the negative effects of media on children. This study aims to describe the phenomenon of digital parenting in relation to the influence of parents' knowledge and attitudes on parental mediation in digital parenting. To this end, a quantitative approach utilizing a survey method was employed. The population of this study comprises parents with children aged 0–7 years residing in Bandung City. A multistage random sampling technique was used to select the sample. A total of 407 parents of children aged 0–7 years participated as respondents in this study. The respondents' characteristics varied widely in terms of age, education level, occupation, and residence. Data were collected using a questionnaire with a Likert scale, distributed via Google Forms. The results indicate that parents' tendency to mediate their children's interactions with online media falls into the moderate category. Parents' knowledge of digital parenting is not yet comprehensive and has not significantly impacted the practice of parental mediation. A significant effect of knowledge on parental mediation was found, mediated by attitudes.